2018
DOI: 10.1002/chem.201801028
|View full text |Cite
|
Sign up to set email alerts
|

A Switch from Mechanistic Competition Mediated by a Combination of Temperature and Concentration Effects in the Oxidation Reaction of [FeII(N4Py/TPA)](OTf)2

Abstract: The formation of [(N4Py)Fe =O] species was accomplished by the reaction of [Fe (N4Py)] with 20 equivalents of tBuO H (TBHP, 70 % in H O). The temperature, [Fe (N4Py)] -concentration and H O-concentration in anhydrous TBHP (5.5 m in decane) dependences of its yields and rates were analyzed to indicate that the proton migration from [(N4Py)Fe -HOOtBu] to [(N4Py)Fe -OO HtBu] is the rate-determining step followed by rapid heterolytic O-O bond cleavage of Fe -OO HtBu to Fe =O complex. The formation of [(TPA)Fe =O] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…92,121,321−328 In addition, subsequent studies on nonheme iron complexes investigated the environmental effects such as solvent and temperature on structure and reactivity. 329,330 Early DFT studies conducted by de Visser, Shaik, and their co-workers suggested that the chemoselectivity originates from the activation energy (E a ) for epoxidation and allylic hydroxylation of iron(IV)oxo-porphyrin π-cation radical 46,331 and that the enthalpy of activation (ΔH ‡ ) dominates over the entropy of activation (ΔS ‡ ) parameter. Moreover, a strong effect on the regioselectivity on the choice of the axial ligand and polarity of the solvent was found.…”
Section: Biomimetic Studies Onmentioning
confidence: 99%
See 1 more Smart Citation
“…92,121,321−328 In addition, subsequent studies on nonheme iron complexes investigated the environmental effects such as solvent and temperature on structure and reactivity. 329,330 Early DFT studies conducted by de Visser, Shaik, and their co-workers suggested that the chemoselectivity originates from the activation energy (E a ) for epoxidation and allylic hydroxylation of iron(IV)oxo-porphyrin π-cation radical 46,331 and that the enthalpy of activation (ΔH ‡ ) dominates over the entropy of activation (ΔS ‡ ) parameter. Moreover, a strong effect on the regioselectivity on the choice of the axial ligand and polarity of the solvent was found.…”
Section: Biomimetic Studies Onmentioning
confidence: 99%
“…As discussed above, the cytochromes P450 form a reactive Cpd I species in their catalytic cycle that performs the oxygen atom transfer reaction to substrates. Interestingly, the reaction of P450 with cyclohexene produces both an epoxidation product and an allylic hydroxylation product. ,, Synthetic iron-porphyrin models have been studied over the years to understand the chemoselectivity of these enzymatic systems which was found to be dependent on external factors including the choice of axial ligands, solvated ions, solvents, and temperature. ,, In addition, subsequent studies on nonheme iron complexes investigated the environmental effects such as solvent and temperature on structure and reactivity. , Early DFT studies conducted by de Visser, Shaik, and their co-workers suggested that the chemoselectivity originates from the activation energy ( E a ) for epoxidation and allylic hydroxylation of iron­(IV)­oxo-porphyrin π-cation radical , and that the enthalpy of activation (Δ H ‡ ) dominates over the entropy of activation (Δ S ‡ ) parameter. Moreover, a strong effect on the regioselectivity on the choice of the axial ligand and polarity of the solvent was found.…”
Section: Biomimetic Studies On Second-coordination Sphere and Seconda...mentioning
confidence: 99%